2018
DOI: 10.5146/tjpath.2018.01432
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of egfr-1, mmp-3, and mmp-9 in spontaneous abortions, induced abortions, and tubal pregnancies

Abstract: Objective: The purpose of our study was to assess trophoblastic and uterine sufficiency in miscarriage pathogenesis with immunohistochemical methods and to determine if they could be used as a screening tool for the risk of miscarriage in the future. Material and Method: Placental tissue specimens that were comprised of 20 spontaneous abortions, 23 voluntarily terminated (induced) abortions, and 12 tubal pregnancies were included in this study. Trophoblastic cells and implantation area were evaluated for stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…They have found a significant association between rs35068180 polymorphism of MMP3 gene and the pregnancy loss. The findings of this study are in keeping with the reports of Balci and Özdemir [31].…”
Section: Discussionsupporting
confidence: 92%
“…They have found a significant association between rs35068180 polymorphism of MMP3 gene and the pregnancy loss. The findings of this study are in keeping with the reports of Balci and Özdemir [31].…”
Section: Discussionsupporting
confidence: 92%
“…MMP-3, MMP-10) and type I and II transmembrane metalloproteinases (Nagase et al 2006 ). In particular, altered MMP-1, -2, -3 and -9 regulation during placentation may lead to placental disease such as pregnancy loss (Balci and Ozdemir 2019 ), preterm delivery (Sundrani et al 2012 ), preeclampsia (PE) (Sahay et al 2018 ) and intra-uterine growth restriction (IUGR) (Swierczewski et al 2012 ). A role for ciliary neurotrophic factor (CNTF) in MMP modulation has been demonstrated in murine neuroblastoma cell models, where CNTF downregulated MMP-2, thus potentially to affecting invasive behaviour (Sartor et al 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, another study noticed that women who had taken resveratrol exhibited lower endometrial TNF-α2 and VEGF concentrations [ 116 ]. Importantly, since all of these above-mentioned molecules were described as factors deteriorating reproductive outcomes [ 118 , 119 , 120 ], resveratrol seems to play an important role in the regulation of eutopic endometrium functioning and help to improve its quality. Another study led by Maia et al found that resveratrol at a dose of 30 mg combined with oral contraceptive pills resulted in decreased COX-2 and aromatase endometrial expressions in comparison to an oral contraceptive pill treatment alone [ 117 ].…”
Section: The Impact Of Selected Antioxidants On Endometriosis-related...mentioning
confidence: 99%